"... und nahm die Tochter Levis". Noch einmal zu Ex 2,1 als Motivation der Aussetzung des Mose: "Seine Geburt war unordentlich ..." - wirklich? - Gerhards, Meik (Biblische Notizen, 2012)
K. Schmid and E. Otto have suggested that the expression „a man from the house of Levi took the daughter of Levi“ (Ex 2,1) showed that Moses was born illegitimately, and that the illegitimacy caused his mother to expose the child. If this interpretation were right, Ex 2,1 could have been the beginning of an originally independent Exodus narrative. The paper discusses the evidence put forward by Schmid and Otto and finally refutes their interpretation.